Shadow warriors : inside the Special Forces - Clancy, Tom, 1947-2013.; Stiner, Carl.; Koltz, Tony. (New York : G.P. Putnam's Sons, 2002)
A look at the U.S. military Special Forces, during the last five decades, through the eyes of retired general Carl Stiner, who has spent many years leading America's Special Forces in such missions as Desert Storm and the Panama invasion.
Monday, October 7, 1985 -- Pioneers -- Warriors' warrior -- Country Carl -- Few are called, fewer are chosen -- Vietnam -- Between the wars - The Lebanon tragedy -- The Achille Lauro strike -- Panama : Operation Blue Spoon -- Panama : Operation Just Cause -- Shadows in the storm -- Bulldog and his pack : an incident in the war -- The face of the future -- Tuesday, September 11, 2001.
Includes bibliographical references (p. [535]-537) and index.
Read by George DiCenzo.
Keywords: Special forces (Military science) -- United States; U.S. Special Operations Command; Low-intensity conflicts (Military science); United States. -- Army. -- Special Forces; USA -- Heer -- Special Forces; Geschichte 1961-2000.; Erlebnisbericht